Penerapan Media Poster Digital Berbasis Project Based Learning Terintegrasi Tri-N Untuk Meningkatkan Keaktifan Belajar Pendidikan Pancasila - Firdausia, Luftia; Wibawa, Sutrisna (Jurnal Kewarganegaraan, 2024)
AbstractThis research aims to determine the application of digital poster media based on the Tri-N integrated Project Based Learning model on students' active learning in Pancasila Education subjects in 4th of Karangnongko 1 State Elementary School. This research is descriptive qualitative research. The subjects of this research were 4th students. Data collection techniques in this research were carried out using interviews, observation, questionnaires, and documentation. The data analysis techniques used in this research are data reduction, data display, and drawing conclusions. The importance of implementing the Tri-N integrated Project Based Learning model with digital poster media means that students have no difficulty in asking, answering and thinking activities. The research results based on interviews with teachers say that students are more active with the application of digital poster media based on the Tri-N integrated Project Based Learning model. Based on the research results, it can be seen that the application of digital poster media based on the Tri-N integrated Project Based Learning model can increase student learning activity in Pancasila Education subjects. The teacher made the digital poster media entitled "Aku Peduli Diriku" using the Canva application to create an attractive digital poster for students.---------------------Abstrak Penelitian bertujuan untuk mengetahui penerapan media poster digital berbasis model pembelajaran Project Based Learning terintegrasi Tri-N terhadap keaktifan belajar siswa pada pelajaran Pendidikan Pancasila di kelas IV SD Negeri Karangnongko 1. Penelitian ini ialah penelitian deskriptif kualitatif. Subjek penelitian ini ialah siswa kelas IV. Teknik pengumpulan data pada penelitian ini dilakukan dengan metode: wawancara, observasi, kuesioner serta dokumentasi. Teknik analisis data yang dipergunakan pada penelitian ini ialah display data, reduksi data, serta penarikan kesimpulan. Pentingnya penerapan media poster digital berbasis Project Based Learning terintegrasi Tri-N menjadikan siswa tidak kesulitan dalam aktivitas bertanya, menjawab, dan berdiskusi. Hasil penelitian berlandaskan wawancara dengan guru mengungkapkan yakni siswa lebih aktif dengan implementasi media poster digital berbasis model pembelajaran PjBL terintegrasi Tri-N. Berlandaskan hasil penelitian dapat diketahui bahwa penerapan media poster digital berbasis Project Based Learning terintegrasi Tri-N mampu menaikkan keaktifan belajar siswa pada mata pelajaran Pendidikan Pancasila. Media poster digital yang berjudul “Aku Peduli Diriku” dibuat guru melalui aplikasi canva sehingga terwujud poster digital yang menarik untuk siswa.